Layer-dependent anisotropic frictional behavior in two-dimensional monolayer hybrid perovskite/ITO layered heterojunctions - Bi, Sheng (2021)
Two-dimensional (2D) organic-inorganic hybrid perovskites, which possess outstanding optical and electrical properties, are promising semiconductor materials that have attracted significant interest in widespread applications. The frictional behavior of 2D perovskite materials with other transparent conductive materials, such as indium tin oxide (ITO), offers promising developments in optoelectronic devices. Therefore, the understanding of this frictional behavior is essential. Atomic force microscopy (AFM) is employed here to measure the frictional behavior between the (001) plane of the 2D organic-inorganic hybrid (C₄H₉NH₃)₂PbBr₄ perovskite and the (111) plane of the ITO. The experimental analyses characterizing the nature of the friction in a single-crystalline heterojunction are reported. Based on the results of the analyses of interfaces between 2D monolayer perovskites and ITO, a strong anisotropy of friction is clearly demonstrated. The anisotropy of friction is observed as a four-fold symmetry with low a frictional coefficient, 0.035, in misaligned contacts, and, 0.015, in aligned contacts in the heterojunction configuration. In addition, atomistic simulations reveal underlying frictional mechanisms in the dynamical regimes. A new phenomenon discovered in the studies establishes that the measured frictional anisotropy surprisingly depends on the number of atomic layers in the 2D perovskite. The frictional anisotropy decreases significantly with the increase in the number of layers up to 16 layers, and then it becomes independent of the thickness. Our results are predicted to be of a general nature and should be applicable to other 2D hybrid perovskite heterojunction configurations, and thus, furthers the development of adaptive and stretchable optoelectronic nanodevices.